Secondary battery and electronic device

By using tape and an electrolyte containing fluoroalkyl in the secondary battery, the problem of insufficient wettability of the electrolyte is solved, and a stable SEI film is formed, which significantly improves the circulation performance and safety of the battery.

CN119890400APending Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510374903.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The inadequate wetting of the electrolyte in the secondary battery leads to the inability of certain areas of the electrode material to effectively participate in the electrochemical reaction, affecting the cycle stability and safety of the battery.

Method used

By using tape and specific electrolytes in secondary batteries, including compounds of formula I containing fluoroalkyl groups, the wetting properties of the electrolyte are improved, and a stable solid electrolyte interface film (SEI) is formed on the surface of the negative electrode to reduce the interface impedance.

Benefits of technology

It effectively improves the wetting and circulation performance of the secondary battery, extends the service life of the battery, reduces the risk of growth and hard expansion of lithium dendrites, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890400A_ABST
    Figure CN119890400A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage, and relates to a secondary battery and an electronic device. The secondary battery comprises an electrode assembly with a lamination structure, gummed paper and electrolyte, wherein the electrode assembly is provided with an upper surface, a lower surface and a side surface; the gummed paper comprises a first attaching part attached to the upper surface, a second attaching part attached to the side surface and a third attaching part attached to the lower surface; the number of the gummed paper is larger than or equal to 2, the sum of the widths of the gummed paper is A cm, the outer perimeter of the electrode assembly is B cm, and A / B is larger than or equal to 0.04 and smaller than or equal to 0.7; the electrolyte comprises a compound shown in the formula I, R1 and R2 are independently selected from C1-C6 alkyl groups which are not substituted or substituted by fluorine atoms, R1 and R2 at least contain one fluorine atom, the mass content of the compound shown in the formula I is X% based on the mass of the electrolyte, and X is larger than or equal to 35 and smaller than or equal to 72. Through cooperation of the gummed paper and the electrolyte, the wettability of the electrolyte in the secondary battery can be effectively improved, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, also known as storage batteries, have been increasingly widely used due to their repeated charge and discharge capabilities, high energy density, low self-discharge rate, and no memory effect.

[0003] The wettability of the electrolyte is an important factor affecting the performance of secondary batteries. Incomplete wettability will cause certain areas of the electrode material to be unable to effectively participate in the electrochemical reaction, uneven current density distribution, and may even cause the growth of lithium dendrites, increasing the risk of battery short circuit and fire. Poor wettability will also cause the formed electrolyte interface film (SEI) to be unstable, affecting the cycle stability of the battery. Therefore, how to improve the wettability of the electrolyte and improve the cycle performance of the battery has become an urgent problem to be solved in the practical application of secondary batteries. Summary of the invention

[0004] In view of this, the present application provides a secondary battery and an electronic device, which can effectively improve the wettability of the secondary battery electrolyte and enhance the cycle performance of the battery through the combination of adhesive tape and electrolyte. In a first aspect, the present application provides a secondary battery, comprising an electrode assembly of a laminated structure, adhesive tape and an electrolyte, wherein the electrode assembly has an upper surface and a lower surface arranged opposite to each other, and a side surface connecting the upper surface and the lower surface; the adhesive tape comprises a first bonding portion, a second bonding portion and a third bonding portion, wherein the first bonding portion is bonded to the upper surface, the second bonding portion is bonded to the side surface, and the third bonding portion is bonded to the lower surface; the number of adhesive tapes is greater than or equal to 2 sheets, the sum of the widths of the adhesive tapes is A cm, the outer perimeter of the electrode assembly 1 is B cm, and 0.04≤A / B≤0.7; the electrolyte comprises a compound of formula I:

[0005] Formula I; Wherein, R1 and R2 are each independently selected from unsubstituted or fluorine-substituted C1-C6 alkyl groups, and at least one fluorine atom is contained in R1 and R2, and the mass content of the compound of formula I is X%, 35≤X≤72, based on the mass of the electrolyte. The use of adhesive tape and electrolyte can effectively improve the wettability of the secondary battery described in the present application and improve the cycle performance of the battery. In some preferred embodiments, when 0.06≤A / B≤0.45, and / or 40≤X≤60, the improvement effect of the wettability and cycle performance of the battery is better.

[0006] In some embodiments, the width of the single piece of adhesive tape is 0.2 cm to 10 cm. Controlling the width of the single piece of adhesive tape within this range can prevent the single piece of adhesive tape from being too narrow and easily damaged, and from being too wide to affect the infiltration of the electrolyte.

[0007] In some embodiments, in order to prevent the adhesive tape from being too close to each other and affecting the infiltration of the electrolyte, the interval between any two adhesive tapes on the side surface is greater than or equal to 0.3 cm.

[0008] In some embodiments, the compound of formula I includes at least one of ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, monofluoromethyl acetate, methyl trifluoroacetate or propyl difluoroacetate. The above compounds can not only reduce the viscosity of the electrolyte, but also preferentially decompose on the surface of the negative electrode to form a LiF-rich SEI film, and LiF has high ionic conductivity and mechanical strength, can inhibit the growth of lithium dendrites, and prolong the cycle life.

[0009] In some preferred embodiments, the width of a single piece of adhesive tape is 0.8 cm to 8 cm. By controlling the width of a single piece of adhesive tape within this range, better wetting can be achieved while more effectively utilizing the adhesive tape.

[0010] In some embodiments, the secondary battery shell in the present application is a steel shell. In a steel shell battery, hard expansion may cause the battery shell to deform or even rupture, causing the battery to short-circuit or even cause safety problems. The present application scheme can improve the wettability of the battery, reduce the uneven volume change of the electrode material during the charging and discharging process, and effectively reduce the risk of hard expansion of the steel shell battery.

[0011] In some embodiments, the adhesive tape includes a substrate layer and an adhesive layer, and the adhesive layer is disposed on any surface of the substrate layer along its thickness direction; the substrate layer includes at least one of polyethylene terephthalate, polyimide or polypropylene, and the adhesive layer includes at least one of acrylic resin, polyethylene glycol or polymethyl methacrylate. The substrate of the above materials has a certain mechanical strength and good insulation and temperature resistance, which can provide the necessary mechanical strength and support for the adhesive tape, so that it is not easy to deform or damage during use; the adhesive layer material has good viscosity, and has good anti-aging, heat resistance and thermal stability, so that the adhesive tape can be firmly attached to the electrode assembly.

[0012] In some embodiments, the adhesive tape satisfies at least one of the following conditions: (1) the thickness of the adhesive tape is 8 μm to 40 μm; (2) the thickness of the substrate layer is 5 μm to 30 μm; (3) the thickness of the adhesive layer is 3 μm to 10 μm. The above configuration allows the adhesive tape to have certain mechanical properties while not being too thick to affect the energy density and structural stability of the battery.

[0013] In some embodiments, the electrolyte includes at least one of the following additives: lithium difluorophosphate, triethyl phosphate, triethyl borate, vinyl sulfate, trimethyl borate, methyl ethanesulfonate, ethyl ethanesulfonate, methyl propyl sulfonate, isopropyl ethanesulfonate or methyl 1-butanesulfonate. Based on the mass of the electrolyte, the mass content of the above additives is 0.5% to 5%. By adding the above additives and controlling the additives within a certain range, the impedance of the battery can be significantly reduced, and the charge transfer resistance can be effectively reduced by forming a stable SEI film, inhibiting the decomposition of the electrolyte and protecting the electrode surface, thereby improving the overall performance of the battery.

[0014] In a second aspect, the present application provides an electronic device, comprising the secondary battery described in any of the aforementioned schemes.

[0015] The beneficial effects of this application are as follows: The present application provides a secondary battery, comprising an electrode assembly of a laminated structure, adhesive tape and an electrolyte, wherein the electrode assembly comprises an upper surface and a lower surface arranged opposite to each other, and a side surface connecting the upper surface and the lower surface; the adhesive tape comprises a first bonding portion, a second bonding portion and a third bonding portion, wherein the first bonding portion is bonded to the upper surface, the second bonding portion is bonded to the side surface, and the third bonding portion is bonded to the lower surface; the number of adhesive tapes is greater than or equal to 2 sheets, the sum of the widths of each sheet of adhesive tape is A cm, the outer circumference of the electrode assembly is B cm, and 0.04≤A / B≤0.7; the electrolyte comprises a compound of formula I, wherein R1 and R2 are each independently selected from a C1-C6 alkyl group that is unsubstituted or substituted with a fluorine atom, and at least one fluorine atom is contained in R1 and R2, and the mass content of the compound of formula I is X%, 35≤X≤72, based on the mass of the electrolyte. The present application controls the sum of the widths of the adhesive tape within a certain range, which can not only enhance the stability of the electrode assembly, but also enable the electrolyte to be replenished in time during the battery cycle, thereby improving the wettability and cycle performance of the battery; by adding the compound of formula I to the electrolyte, on the one hand, the viscosity of the electrolyte can be reduced, allowing the electrolyte to be better infiltrated, and on the other hand, the compound of formula I can form a stable and dense solid electrolyte interface film (SEI) rich in lithium fluoride on the surface of the negative electrode, inhibiting further reaction of lithium metal and solvent, and reducing the interfacial impedance of the battery, improving the transmission efficiency of lithium ions at the electrode / electrolyte interface, thereby improving the cycle performance of the battery. The use of adhesive tape and electrolyte in combination can effectively improve the wettability of the secondary battery described in the present application and improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic diagram of a secondary battery according to an embodiment of the present application at a first viewing angle; Figure 2 A schematic diagram of a secondary battery according to another embodiment of the present application at a first viewing angle; Figure 3 A schematic diagram of a secondary battery according to another embodiment of the present application at a second viewing angle; Figure 4 A schematic diagram of a secondary battery according to another embodiment of the present application at a second viewing angle; Figure 5 This is a schematic diagram of the adhesive tape structure of an implementation scheme of the present application.

[0017] Reference numerals: 1-electrode assembly; 11-ear; 101-upper surface; 102-lower surface; 103-side surface; 103a-first side surface; 103b-second side surface; 103c-third side surface; 103d-fourth side surface; 2-adhesive tape; 21-base material layer; 22-adhesive layer; 201-first bonding part; 202-second bonding part; 203-third bonding part. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0019] In this application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inside", "outside", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions and positional relationships shown in the drawings or the positions or positional relationships in which the products of this application are usually placed when used. These terms are mainly used to better describe this application and its embodiments, and are not used to limit the indicated devices, elements or components to have specific positions, or to be constructed and operated in specific positions.

[0020] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0021] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0022] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.

[0023] During the production of secondary batteries, materials such as electrode sheets and diaphragms need to be accurately fixed and positioned to ensure the stability and consistency of the internal structure of the battery. Using adhesive tape before injection can prevent the battery structure from shifting or deforming during the injection process, ensuring the smooth progress of the injection process. However, the barrier of the adhesive tape to the electrolyte will also affect the infiltration of the electrolyte. The inventors have found that when the ratio of the sum of the width of the adhesive tape to the outer circumference of the electrode assembly is controlled within a certain range, the stability of the electrode assembly can be enhanced, and the electrolyte can be diffused into the electrode assembly through the electrode assembly where the adhesive tape is not set, so that the electrolyte can be replenished in time during the battery cycle, and the wettability of the battery can be improved. Good wettability can improve the capacity utilization rate, charge and discharge rate performance, cycle stability and safety performance of the battery, extend the service life of the battery, and meet the needs of various application scenarios. The inventors also found that adding a compound of formula I to the electrolyte and cooperating with the above-mentioned adhesive tape system can further improve the wettability of the battery, and the cycle performance of the battery has also been significantly improved. On the one hand, the compound of formula I contains a fluorinated alkyl group, and the strong electronegativity of the fluorine atom causes the molecular polarity of the compound of formula I to be relatively low. The solvent-repellent effect of the fluorinated group causes the molecular arrangement to be looser, further reducing the interaction force. Therefore, the compound of formula I can reduce the viscosity of the electrolyte, especially when combined with the above-mentioned adhesive tape system, it can make the electrolyte better infiltrated; on the other hand, the compound of formula I can form a stable and dense solid electrolyte interface film (SEI) rich in lithium fluoride on the surface of the negative electrode, inhibiting the further reaction of lithium metal and solvent, and reducing the interfacial impedance of the battery, thereby improving the transmission efficiency of lithium ions at the electrode / electrolyte interface, thereby improving the cycle performance of the battery.

[0024] Based on this, the present application provides a secondary battery and an electronic device, which can effectively improve the wettability of the secondary battery electrolyte and enhance the cycle performance of the battery through the combination of adhesive tape and electrolyte. In the first aspect, the present application provides a secondary battery, please refer to Figures 1 to 4, comprising an electrode assembly 1 of a laminated structure, adhesive tape 2 and an electrolyte, the electrode assembly 1 having an upper surface 101 and a lower surface 102 arranged opposite to each other, and a side surface 103 connecting the upper surface 101 and the lower surface 102; the adhesive tape 2 comprises a first bonding portion 201, a second bonding portion 202 and a third bonding portion 203, the first bonding portion 201 is bonded to the upper surface 101, the second bonding portion 202 is bonded to the side surface 103, and the third bonding portion 203 is bonded to the lower surface 102; the number of adhesive tapes 2 is greater than or equal to 2 pieces, the sum of the widths of each piece of adhesive tape 2 is A cm, the outer circumference of the electrode assembly 1 is B cm, 0.04≤A / B≤0.70; the electrolyte comprises a compound of formula I, wherein R1 and R2 are each independently selected from a C1-C6 alkyl group that is unsubstituted or substituted with a fluorine atom, and at least one fluorine atom is contained in R1 and R2, and the mass content of the compound of formula I is X%, 35≤X≤72 based on the mass of the electrolyte.

[0025] Formula I Exemplarily, the value of A / B can be 0.04, 0.08, 0.15, 0.20, 0.30, 0.40, 0.55, 0.60, 0.62, 0.70 or a range consisting of any two of the above values; the value of X can be 35, 38, 44, 51, 57, 63, 70, 72 or a range consisting of any two of the above values.

[0026] It should be noted that the width in this application refers to the projection width of the second laminating portion 202 of the adhesive tape 2 on the side surface 103 of the electrode assembly 1. For details, see Figure 1 , d 1 to d 5 is the width of the adhesive tape 2 in this application, and the sum of the widths of each piece of adhesive tape 2 is d 1. d 2. d 3. d 4. d 5; the outer perimeter of the electrode assembly 1 refers to the sum of the lengths of the side surfaces 103 of the electrode assembly 1. Specifically, see Figure 2 , l 1 to l 4 are respectively the lengths of the first side surface 103a, the second side surface 103b, the third side surface 103c, and the fourth side surface 103d of the electrode assembly 1, l 1. l 2. l 3. l 4 is the outer circumference of the electrode assembly 1. The adhesive tape 2 may be affixed perpendicularly to the upper surface 101 and the lower surface 102 of the electrode assembly 1, or may not be perpendicularly affixed, and this application does not limit this.

[0027] The inventors found that: a certain mass concentration of the compound of formula I can reduce the viscosity of the electrolyte system and enhance the wetting, but if the content of the compound of formula I is too high, the strong electronegativity of the fluorine atom will make it easier for the molecules to form hydrogen bonds or other types of interactions. This enhanced intermolecular force will reduce the fluidity of the electrolyte and increase the viscosity, thereby affecting the wettability of the electrolyte and the cycle performance of the battery. That is to say, under certain other conditions, in order to achieve a good wetting effect, if the content of the compound of formula I in the electrolyte is high, more space is needed on the electrode assembly 1 for the electrolyte to be immersed, and the electrolyte is replenished during the battery cycle, that is, the contact between the adhesive tape 2 and the side surface 103 of the electrode assembly 1 should be as small as possible, that is, the sum of the widths of the adhesive tape 2 should be as small as possible. However, too little adhesive tape 2 will affect the stability of the electrode assembly 1. Therefore, it is necessary to consider the ratio of the sum of the widths of the adhesive tape 2 to the outer perimeter of the electrode assembly 1 and the content of the compound of formula I in the electrolyte in a coordinated manner to achieve better wetting. When the electrolyte evenly infiltrates the electrode, the interface impedance is reduced, and the ion transmission efficiency at the electrode / electrolyte interface is improved, thereby improving the cycle performance of the battery. A certain content of the compound of formula I can also significantly improve the cycle performance of the battery by forming a stable SEI film, improving the antioxidant property of the electrolyte, optimizing the lithium ion transmission kinetics, inhibiting the formation of lithium dendrites, and improving high and low temperature performance. The inventor further found that when the ratio of the sum of the width of the adhesive tape 2 to the outer perimeter of the electrode assembly 1 and the content of the compound of formula I in the electrolyte are both within the above-given range, better infiltration of the battery electrolyte and better cycle performance can be achieved.

[0028] In some preferred embodiments, when 0.06≤A / B≤0.45, and / or 40≤X≤60, the improvement effect of the wettability and cycle performance of the battery is better. For example, the value of A / B can be 0.06, 0.13, 0.15, 0.22, 0.28, 0.31, 0.35, 0.45 or a range consisting of any two of the above values; the value of X can be 40, 42, 45, 51, 58, 60 or a range consisting of any two of the above values.

[0029] In some embodiments, the width of the single piece of adhesive tape 2 is 0.2 cm to 10 cm. By controlling the width of the single piece of adhesive tape 2 within this range, the single piece of adhesive tape 2 can be neither too narrow to be easily damaged nor too wide to affect the infiltration of the electrolyte. Exemplarily, the width of the single piece of adhesive tape 2 can be any value within the above range, including but not limited to 0.2 cm, 0.8 cm, 1.2 cm, 1.6 cm, 3 cm, 5 cm, 8 cm, 10 cm, etc.

[0030] In some embodiments, the interval between two adjacent adhesive tapes 2 on the side surface 103 is greater than or equal to 0.3 cm. Controlling the adhesive tapes 2 to be dispersed and pasted according to this condition can achieve a better fixing effect with less adhesive tapes 2. The appropriate interval between adhesive tapes 2 can not only reduce the waste of adhesive tapes 2, but also reduce or avoid the accumulation of electrolyte at the interval caused by the adhesive tapes 2 being too close when the injection speed is fast, affecting the wettability of the electrolyte and reducing the risk of battery electrical performance.

[0031] In some embodiments, the compound of formula I includes at least one of ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, methyl trifluoroacetate or propyl difluoroacetate. Taking lithium batteries as an example, the carboxyl group in the above-mentioned compound can enhance the interfacial stability between the electrolyte and the electrode and reduce the occurrence of side reactions by interacting with the electrode surface; through coordination with lithium ions, the desolvation energy barrier of lithium ions can be reduced, thereby improving the transmission kinetics of lithium ions. At the same time, the above-mentioned compound can increase the content of F element in the electrolyte, reduce the viscosity of the electrolyte, further enhance the overall antioxidant property of the solvent, form a CEI film rich in LiF, and improve the cycle performance of the secondary battery.

[0032] In some preferred embodiments, the width of the single piece of adhesive tape 2 is 0.8 cm to 8 cm. Exemplarily, the width of the single piece of adhesive tape 2 can be any value within the above range, including but not limited to 0.8 cm, 1.1 cm, 2 cm, 4 cm, 6 cm, 8 cm, etc. By controlling the width of the single piece of adhesive tape 2 within this range, the adhesive tape 2 can be used more effectively and better infiltration can be achieved.

[0033] In some embodiments, the secondary battery shell in the present application is a steel shell. Compared with soft-pack batteries, steel-shell batteries are hard shells with poor deformation force. When the battery undergoes hard expansion, it may cause the steel-shell battery shell to deform or even rupture, causing the battery to short-circuit or even cause safety problems. The present application scheme can improve the wettability of the battery, reduce the uneven volume change of the electrode material during the charging and discharging process, effectively reduce the risk of hard expansion of the steel-shell battery, and improve the battery cycle performance.

[0034] In some embodiments, Figure 5As shown, the adhesive tape 2 includes a substrate layer 21 and an adhesive layer 22, and the adhesive layer 22 is arranged on any surface of the substrate layer 21 along its thickness direction; the substrate layer 21 includes at least one of polyethylene terephthalate, polyimide or polypropylene, and the adhesive layer 22 includes at least one of acrylic resin, polyethylene glycol or polymethyl methacrylate. The substrate of the above material has a certain mechanical strength and good insulation and temperature resistance, which can provide the necessary mechanical strength and support for the adhesive tape 2, so that it is not easy to deform or damage during use; and the adhesive layer 22 of the above material has good viscosity, and has good anti-aging, heat resistance and thermal stability, so that the adhesive tape 2 can be firmly attached to the electrode assembly 1.

[0035] In some embodiments, the adhesive tape 2 satisfies at least one of the following conditions: (1) the thickness of the adhesive tape 2 is 8 μm to 40 μm; (2) the thickness of the substrate layer 21 is 5 μm to 30 μm; (3) the thickness of the adhesive layer 22 is 3 μm to 10 μm. The above configuration allows the adhesive tape 2 to have certain mechanical properties while not being too thick to affect the energy density and structural stability of the battery. Exemplarily, the thickness of the adhesive tape 2 is any value within the above range, including but not limited to 8 μm, 10 μm, 16 μm, 20 μm, 22 μm, 25 μm, 30 μm, 40 μm, etc.; the thickness of the substrate layer 21 is any value within the above range, including but not limited to 5 μm, 6 μm, 12 μm, 17 μm, 22 μm, 28 μm, 30 μm, etc.; the thickness of the adhesive layer 22 is any value within the above range, including but not limited to 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0036] In some embodiments, the electrolyte includes at least one of the following additives: lithium difluorophosphate, triethyl phosphate, triethyl borate, vinyl sulfate, trimethyl borate, methyl ethanesulfonate, ethyl ethanesulfonate, methyl propyl sulfonate, isopropyl ethanesulfonate or methyl 1-butanesulfonate. Based on the mass of the electrolyte, the mass content of the above additives is 0.5% to 5%. Exemplarily, the mass content of the above additives is any point value in the above range, including but not limited to 0.5%, 1.3%, 1.5%, 2.0%, 2.4%, 3.2%, 4.0%, 4.5%, 5.0%, etc. By adding the above additives and controlling the content of the additives within a certain range, the impedance of the battery can be significantly reduced, and the charge transfer resistance can be effectively reduced by forming a stable SEI film, inhibiting the decomposition of the electrolyte and protecting the electrode surface, thereby improving the overall performance of the battery.

[0037] The electrolyte can play a role in transmitting lithium ions and electrons, ensuring the formation of a pathway inside the secondary battery. The electrolyte usually contains lithium salts, solvents and additives. Specifically, the lithium salt can be dissolved in the solvent to form an ion conductor, used as a conductive medium and a lithium ion transmission medium; the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorooxalatoborate), lithium bis(fluorosulfonylimide) and the like. The solvent can dissolve the lithium salt and the additive, and the solvent can be at least one of carbonate, carboxylic acid ester, ether, alcohol, etc., wherein the carbonate can be divided into cyclic carbonate, linear carbonate, etc. Cyclic carbonate specifically includes but is not limited to at least one of ethylene carbonate, propylene carbonate, etc.; linear carbonate specifically includes but is not limited to at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, etc.; carboxylic acid ester includes but is not limited to at least one of methyl formate, methyl acetate, methyl butyrate, ethyl propionate, propyl propionate, propyl acetate, etc.; ethers include but are not limited to at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, etc.; alcohols include but are not limited to at least one of ethanol, ethylene glycol, glycerol, etc.

[0038] In the present application, the electrode assembly includes a positive electrode, a negative electrode and a separator.

[0039] The present application has no special restrictions on the positive electrode, as long as the purpose of the present application can be achieved. For example, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode active material layer located on at least one surface of the positive electrode current collector" means that the positive electrode active material layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.

[0040] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0041] The positive electrode active material layer of the present application includes a positive electrode active material. The present application has no particular limitation on the type of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide [LiNi 0.90 Co0.05 Mn 0.05 O2 (NCM955), NCM811, NCM622, NCM523, NCM111], lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate. In the present application, the positive active material may also contain non-metallic elements, such as non-metallic elements including at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive current collector and the positive active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5μm to 20μm, and the thickness of the single-sided positive active material layer is 30μm to 120μm.

[0042] In the present application, the positive electrode active material layer may further include a positive electrode binder and a positive electrode conductor. The present application does not particularly limit the type of positive electrode binder in the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0043] The present application has no particular restrictions on the type of positive electrode conductive agent in the positive electrode active material layer, as long as the purpose of the present application can be achieved. In some embodiments, the positive electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the loading amount of the positive electrode active material in the positive electrode sheet is 4.0 mg / cm 2 Up to 10.0 mg / cm 2 .

[0044] In the present application, the secondary battery also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0045] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.).

[0046] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular restrictions on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOx (0.5 <x <1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 5 μm to 16 μm, and the thickness of the single-sided negative electrode active material layer is 30 μm to 120 μm.

[0047] The negative electrode active material layer in the present application may also include a negative electrode binder and a negative electrode conductor, or the negative electrode active material layer may also include a negative electrode binder, a negative electrode conductor and a thickener. The present application has no particular restrictions on the types of negative electrode binders and negative electrode conductors, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of the above-mentioned positive electrode binders, and the negative electrode conductor may include but is not limited to at least one of the above-mentioned positive electrode conductors. The present application has no particular restrictions on the types of thickeners, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder, and the thickener in the negative electrode active material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0048] In the present application, the secondary battery also includes a diaphragm, which is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters [for example, polyethylene terephthalate (PET) film], cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0049] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0050] The secondary battery in the present application also includes a tab, which can lead the current out of the electrode assembly. The tab may include a positive tab and a negative tab, which are connected to the positive current collector substrate and the negative current collector substrate respectively. The tab may be formed by cutting or trimming the current collector substrate, or may be connected by welding. The present application does not limit the number, position, formation method, etc. of the tab.

[0051] The secondary battery of the present application also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components of a secondary battery known in the art. The shell can be a steel shell, an aluminum shell, a plastic shell (such as polypropylene), a composite metal shell (such as a copper-aluminum composite shell) or an aluminum-plastic film, etc.

[0052] The present application does not particularly limit the type of secondary battery, which may include any device that generates an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0053] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing them to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a housing, injecting the electrolyte into the housing and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the housing as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0054] In a second aspect, the present application provides an electronic device, which includes the secondary battery in any of the aforementioned solutions.

[0055] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0056] The following is an example of a lithium-ion battery and the scheme of the present application is described in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from ordinary commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0057] Test methods and equipment: Cycle performance test: Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge it to 4.5V at a constant current of 0.5C, charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Record the initial discharge capacity as C0. Cycle the above charge and discharge steps for 500 cycles, and record the discharge capacity after 500 cycles as C1.

[0058] Cycle capacity retention rate = C1 / C0×100%.

[0059] Wetting test: Place the lithium-ion battery in a 0℃ constant temperature environment and let it stand for 30 minutes to make the lithium-ion battery reach a 0℃ constant temperature state. Charge it to 3.95V at a constant current of 0.5C, place the battery in a 25℃ environment for 4 hours, and test the initial thickness of the battery at this time h1. Place the lithium-ion battery in a 0℃ constant temperature environment and let it stand for 30 minutes to make the lithium-ion battery reach a 0℃ constant temperature state. Charge it to 4.5V at a constant current of 0.5C, charge it at a constant voltage to a current of 0.025C, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Cycle the above charge and discharge steps for 200 times, place the battery in a 25℃ environment for 4 hours, and test the battery thickness at this time h2. Battery thickness growth rate = (h2-h1) / h1×100%.

[0060] Example 1-1 <Preparation of Electrolyte> In a dry argon atmosphere glove box, lithium hexafluorophosphate was dissolved in a solution containing ethyl difluoroacetate and propylene carbonate. Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate was 12.5%, the mass content of ethyl difluoroacetate was 50%, and the balance was propylene carbonate.

[0061] <Preparation of negative electrode sheet> The negative electrode active material artificial graphite, negative electrode conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and negative electrode binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1.5:0.5:1.6, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 30wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10µm, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side, and then the above steps were repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After coating, the negative electrode sheet was cold pressed and cut into a specification of 18 cm×22 cm for standby use.

[0062] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode binder polyvinylidene fluoride (PVDF), and the positive electrode conductive agent Super P are mixed in a mass ratio of 97:1.6:1.4, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and stirred evenly. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 110°C to obtain a positive electrode sheet coated with a single-sided positive electrode active material. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a double-sided positive electrode active material. After the coating is completed, the positive electrode sheet is cold pressed and cut into a positive electrode sheet with a specification of 16 cm×21 cm for standby use.

[0063] <Diaphragm> A polyethylene-polypropylene film with a thickness of 7 μm was used.

[0064] <Preparation of Electrode Assembly> The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a barrier role. The positive and negative electrode sheets and the separator are stacked and formed at one time using a one-time molding technology, and the pole ears are welded to obtain an electrode assembly.

[0065] <Attachment of adhesive tape> Cut five pieces of adhesive tape with widths of 1 cm, 2 cm, 6 cm, 8 cm, and 9 cm, and thickness of 28 μm (the thickness of the substrate layer is 20 μm, and the thickness of the adhesive layer is 8 μm). The interval between any two pieces of adhesive tape should be greater than 0.3 cm. Figure 1 The adhesive tape is pasted on the electrode assembly in the manner shown, and the second pasting portion of the adhesive tape is pasted to the side surface of the electrode assembly.

[0066] <Preparation of lithium-ion batteries> The electrode assembly is placed in an aluminum-plastic film packaging shell, placed in a vacuum oven at 85°C for 12 hours to remove moisture, injected with the prepared electrolyte, and a lithium-ion battery is obtained through vacuum packaging, standing, and formation processes.

[0067] Examples 1-2 to 1-14, Comparative Examples 1-1 to 1-8 The difference from Example 1-1 is that the parameters are adjusted according to Table 1. The performance test results of each embodiment and comparative example are shown in Table 1.

[0068] Table 1

[0069] As can be seen from Table 1, by regulating the electrolyte to include a compound of formula I, the mass percentage of the compound of formula I is between 35% and 72%, and at the same time, regulating the ratio of the sum of the width of the adhesive tape to the outer circumference of the electrode assembly (A / B) between 0.04 and 0.7, the lithium-ion battery has good wettability and cycle performance. In particular, when the mass percentage of the compound of formula I is between 40% and 60%, and / or, A / B is between 0.06 and 0.45, the lithium-ion battery exhibits better wettability and cycle performance. Referring to Examples 1-1 to 1-14, Comparative Examples 1-1 to 1-8, it can be seen that the values ​​of A / B and X must be within the range described in this application to better improve the wettability and cycle performance of the lithium-ion battery. If either of them does not meet the range described in this application, it will affect the wettability and cycle performance of the battery. It should be noted that the battery thickness growth rate is used in this application to characterize the wettability of the battery. The smaller the battery thickness growth rate after cycling in a 0°C environment, the better the electrolyte wets the electrode assembly.

[0070] Comparing Examples 1-1 to 1-6 with Comparative Examples 1-1 and 1-2, it can be seen that the value of A / B has a great influence on the wettability and cycle performance of lithium-ion batteries. Referring to Examples 1-1 to 1-6, when the type and content of the compound of Formula I remain unchanged, when the value of A / B is between 0.04 and 0.7, the cycle capacity retention rate of the lithium-ion battery is 53% to 64%, the battery thickness growth rate is 18% to 26%, and the battery wettability and cycle performance of lithium ions are better as a whole. In particular, when the value of A / B is between 0.06 and 0.45, the cycle capacity retention rate of the lithium-ion battery is 60% to 64%, the battery thickness growth rate is 18% to 23%, and the overall performance of the lithium-ion battery wettability and cycle performance is better.

[0071] In Examples 1 to 5, A / B gradually increased from 0.04 to 0.45, the cycle capacity retention rate of the lithium ion battery gradually increased from 54% to 64%, and the battery thickness growth rate decreased from 25% to 18%. As the value of A / B further increased, in Examples 1-6, the value of A / B increased to 0.7, the cycle capacity retention rate of the lithium ion battery decreased to 53%, the battery thickness growth rate increased to 26%, and the wettability and cycle performance decreased to a certain extent; in Comparative Examples 1-2, the value of A / B increased to 0.8, which exceeded the scope of the present application, the cycle capacity retention rate of the lithium ion battery decreased to 46%, the battery thickness growth rate increased to 30%, and the wettability and cycle performance of the lithium ion battery decreased significantly.

[0072] In Examples 1-1 to 1-6 and Comparative Example 1-1, when the value of A / B drops to 0.03, the cycle capacity retention rate of the lithium-ion battery drops to 46%, and the battery thickness growth rate rises to 31%, that is, the wettability of the lithium-ion battery decreases and the cycle performance decreases. Therefore, when the A / B value of the present application is adjusted within the above range, while maintaining the stability of the electrode assembly, it is beneficial for the adhesive tape and the side surface of the electrode assembly to maintain a suitable contact area, and in combination with the electrolyte system of the present application, it can take into account the improvement of the wettability and cycle performance of the lithium-ion battery.

[0073] Comparing Examples 1-5, 1-7 to 1-10, when the A / B value and the type of the compound of formula I remain unchanged, when the content of the compound of formula I is 35% to 72%, the cycle capacity retention rate of the lithium ion battery is 53% to 64%, the battery thickness growth rate is 18% to 27%, and the lithium ion battery wettability and cycle performance are generally good. Especially when the content of the compound of formula I is 40% to 60%, the cycle capacity retention rate of the lithium ion battery is 60% to 64%, the battery thickness growth rate is 18% to 23%, and the lithium ion battery wettability and cycle performance are better overall.

[0074] In Comparative Example 1-3, the content of the compound of Formula I is 30%, which is less than the minimum value of the content of the compound of Formula I described in the present application. The cycle capacity retention rate of the lithium ion battery is 45%, which is lower than that of Examples 1-7 to 1-10; the battery thickness growth rate is 30%, which is higher than that of Examples 1-7 to 1-10, and the wettability and cycle performance of the lithium ion battery are poor.

[0075] In Comparative Example 1-4, the content of the compound of formula I is 80%, which is greater than the maximum value of the compound of formula I described in the present application, and the cycle capacity retention rate of the lithium ion battery is 48%, which is lower than that of Examples 1-7 to 1-10; the battery thickness growth rate is 31%, which is higher than that of Examples 1-7 to 1-10. It can be seen that the present application regulates the content of the compound of formula I within a suitable range, and cooperates with pasting the adhesive tape in the manner described in the present application, which is conducive to improving the wettability of the electrolyte and the cycle performance of the lithium ion battery.

[0076] Example 2-1 to Example 2-6, Comparative Example 2-1 to Comparative Example 2-2 The difference from Examples 1-5 is that various parameters of the adhesive tape are adjusted according to the parameters shown in Table 2. The performance test results of various embodiments and comparative examples are shown in Table 2.

[0077] Table 2

[0078] As can be seen from Table 2, controlling the width, spacing and thickness of the adhesive tape within the range described in this application, and the number of adhesive tape sheets being greater than or equal to two sheets, can effectively improve the wettability and cycle performance of lithium-ion batteries. The adhesive tape setting described in this application can reduce the damage of the adhesive tape and improve the infiltration of the electrolyte.

[0079] Controlling the dispersed pasting of the adhesive tape 2 can achieve a better fixing effect with less adhesive tape, thereby improving the wettability and cycle performance. Comparing Example 2-2 with Example 2-6, it can be seen that the battery thickness growth rate in Example 2-6 is 24%, which is higher than the 22% in Example 2-2; the cycle capacity retention rate in Example 2-6 is 57%, which is significantly lower than the 69% in Example 2-2. In other words, the adhesive tape spacing setting of the present application can effectively improve the wettability and cycle performance of lithium-ion batteries, especially the cycle performance. Reasonable adhesive tape spacing can not only reduce the waste of adhesive tape, but also reduce or avoid the accumulation of electrolyte at the interval caused by the close adhesive tape spacing when the injection speed is fast, affecting the wettability of the lithium-ion battery and reducing the electrical performance risk of the lithium-ion battery.

[0080] The thickness of the adhesive tape is also related to the improvement of the wettability and cycle performance of the lithium-ion battery. Controlling the thickness of the adhesive tape within the range described in this application can make the adhesive tape have certain mechanical properties and help improve the energy density and structural stability of the lithium-ion battery. Comparing Example 2-2 with Example 2-4 and Example 2-5, it can be seen that the thickness of the adhesive tape within the range of this application can balance the cycle performance and wettability of the lithium-ion battery. Too thin adhesive tape will affect the cycle performance of the lithium-ion battery, and too thick adhesive tape will affect the wettability of the battery.

[0081] Example 3-1 to Example 3-5 The difference from Examples 1-5 is that the content and type of the compound of formula I are adjusted according to the parameters shown in Table 3. The performance test results of each embodiment and comparative example are shown in Table 3.

[0082] Table 3

[0083] In addition to the content of the compound of formula I, the type of the compound of formula I also affects the wettability and cycle performance of the lithium ion battery. From Examples 1-5 and 3-1 to 3-5, it can be seen that when the compound of formula I is selected, the battery thickness growth rate of the lithium ion battery is low and the cycle capacity retention rate is high, indicating that the lithium ion battery has good wettability and cycle performance.

[0084] Example 4-1 to Example 4-9, Comparative Example 4-1 to Comparative Example 4-4 The difference from Example 1-1 is that the outer shell used for the lithium-ion battery is a steel shell, and the parameters are adjusted according to Table 4. The performance test results of each embodiment and comparative example are shown in Table 4.

[0085] Table 4

[0086] As can be seen from Table 4, the scheme described in the present application is also applicable to steel-shell batteries. By regulating the electrolyte to include the compound of formula I, the mass percentage of the compound of formula I is between 35% and 72%, and at the same time, regulating the ratio of the sum of the width of the adhesive tape to the outer circumference of the electrode assembly (A / B) between 0.04 and 0.7, the steel-shell battery has good wettability and cycle performance. In particular, when the mass percentage of the compound of formula I is between 40% and 60%, and / or A / B is between 0.06 and 0.45, the steel-shell battery exhibits better wettability and cycle performance.

[0087] Example 5-1 to Example 5-8 The difference from Example 1-1 is that the content and type of the additives are adjusted according to the parameters shown in Table 5. The performance test results of each embodiment and comparative example are shown in Table 5.

[0088] Table 5

[0089] By comparing Example 1-1 with Example 5-1 to Example 5-8, it can be seen that when the electrolyte also includes the above-mentioned additives, and the type and mass content of the additives are within the range described in the present application, the battery thickness growth rate of the lithium-ion battery is low and the cycle capacity retention rate is high, indicating that adding the above-mentioned additives and controlling the mass content of the additives within a certain range can effectively improve the wettability and cycle performance of the lithium-ion battery.

[0090] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery, characterized in that: An electrode assembly comprising a laminate structure, adhesive tape and an electrolyte, wherein the electrode assembly has an upper surface and a lower surface arranged opposite to each other, and a side surface connecting the upper surface and the lower surface; The adhesive tape comprises a first bonding portion, a second bonding portion and a third bonding portion, the first bonding portion is bonded to the upper surface, the second bonding portion is bonded to the side surface, and the third bonding portion is bonded to the lower surface; the number of the adhesive tapes is greater than or equal to 2, the sum of the widths of the adhesive tapes is A cm, the outer perimeter of the electrode assembly is B cm, and 0.04≤A / B≤0.7; The electrolyte comprises a compound of formula I: Formula I; Wherein, R1 and R2 are each independently selected from unsubstituted or fluorine-substituted C1-C6 alkyl groups, and R1 and R2 contain at least one fluorine atom. Based on the mass of the electrolyte, the mass content of the compound of formula I is X%, 35≤X≤72.

2. The secondary battery according to claim 1, characterized in that: 0.06≤A / B≤0.45, and / or 40≤X≤60.

3. The secondary battery according to claim 1 or 2, characterized in that: The width of a single piece of adhesive tape is 0.2 cm to 10 cm.

4. The secondary battery according to claim 1 or 2, characterized in that: The interval between any two pieces of adhesive tape on the side surface is greater than or equal to 0.3 cm.

5. The secondary battery according to claim 1 or 2, characterized in that: The compound of formula I includes at least one of ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, monofluoromethyl acetate, methyl trifluoroacetate or propyl difluoroacetate.

6. The secondary battery according to claim 3, characterized in that: The width of a single piece of the adhesive tape is 0.8 cm to 8 cm.

7. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery shell is a steel shell.

8. The secondary battery according to claim 1 or 2, characterized in that: The adhesive tape includes a base material layer and an adhesive layer, wherein the adhesive layer is arranged on any surface of the base material layer along its thickness direction; the base material layer includes at least one of polyethylene terephthalate, polyimide or polypropylene, and the adhesive layer includes at least one of acrylic resin, polyethylene glycol or polymethyl methacrylate.

9. The secondary battery according to claim 8, characterized in that: The adhesive tape satisfies at least one of the following conditions: (1) The thickness of the adhesive tape is 8 μm to 40 μm; (2) The thickness of the substrate layer is 5 μm to 30 μm; (3) The thickness of the adhesive layer is 3 μm to 10 μm.

10. The secondary battery according to claim 1 or 2, characterized in that: The electrolyte comprises at least one of the following additives: lithium difluorophosphate, triethyl phosphate, triethyl borate, vinyl sulfate, trimethyl borate, methyl ethanesulfonate, ethyl ethanesulfonate, methyl propylsulfonate, isopropyl ethanesulfonate or methyl 1-butanesulfonate; Based on the mass of the electrolyte, the mass content of the additive is 0.5% to 5%.

11. An electronic device, characterized in that: The electronic device comprises the secondary battery according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Secondary battery and electronic device

    CN117457967A

  • Electrolyte, secondary battery containing electrolyte, battery pack and electric equipment

    CN117832618A

  • Secondary battery and electronic device

    CN117996155A